Emerging market of tobacco - Datta, Dipayan; Ramesh Kumar, S. G.; Aswath Narayanan, M. B.; Leena Selvamary, A.; Sujatha, A. (International Journal Of Community Medicine And Public Health, 2018)
Tobacco industry throughout the world started growing larger and larger. Large firms like British American Tobacco, Imperial Tobacco, China National Tobacco Co. etc. have been manufacturing and exporting tremendous amount of tobacco products. But concurrent research works were also growing to investigate the ill impact of tobacco on health and environment. Since the mid-1960s, strong evidence of the lethal effects of tobacco consumption has led to a sharp decline in official support for producers and manufacturers of tobacco. As the industry is struggling with reduction in smoking rates, huge sales taxes and strict regulations in mature markets, developing economies are offering the emerging markets with better prospects. Ideally, interventions that specifically address a market failure should be implemented as the “best” options. As part of moving towards a more sustainable form of globalization, a global enabling environment linked to local actions should focus on the following strategies: global information management; development of nationally and locally grounded action; global regulation, legal instruments, and foreign policy; and establishment of strong partnerships with purpose.